THE EFFECT OF RADIATION ON DIARRHEA AND DIGESTIVE DISORDERS IN CERVICAL CANCER PATIENS WITH 3D-CRT TECHNIQUE AT MRCCC SILOAM SEMANGGI HOSPITAL: english - Manurip, Gabreal Injelika; Harlis, Yogi Purba; Gitawiarsa, I Putu Pande (HEARTY, 2026)
Cervical cancer is one of the most common cancers in women, with radiotherapy being a primary treatment option, including the use of Three-Dimensional Conformal Radiation Therapy (3D-CRT). Although this technique precisely delivers radiation doses to the target area, exposure to surrounding organs often causes gastrointestinal side effects, particularly diarrhea. This study aimed to evaluate the effect of radiation fractionation on the occurrence of diarrhea in cervical cancer patients treated at MRCCC Siloam Semanggi Hospital. A quantitative descriptive design was applied using questionnaires based on a simplified version of CTCAE v5.0, supported by direct observation and interviews. A total of 10 patients participated, resulting in 50 questionnaire entries collected at the 5th, 10th, 15th, 20th, and 25th fractions. The results showed that most patients experienced mild diarrhea starting from the mid-treatment phase (15th fraction), while some showed fluctuating patterns with two peaks (15th and 25th fractions), and others remained stable with mild symptoms. No patients reached grade 3 (severely affecting daily activities). In conclusion, fractionated radiation exposure was associated with the onset of diarrhea, but symptoms were generally mild to moderate. Regular monitoring and nutritional education are essential strategies to minimize gastrointestinal toxicity and maintain patients’ quality of life during therapy.